PREVENTING HYPERTENSION THROUGH COUNSELLING in PANTEE VILLAGE, INGIN JAYA SUBDISTRICT, ACEH BESAR REGENCY - Hamisah, Irma; Astuti, Wirna Lita; Rinzani, Alif Lia; Nisa, Naziratul; Oktaviani, Aulia (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2025)
Hypertension is a major non-communicable disease and a leading cause of illness and death worldwide, including in Indonesia. A health screening in Gampong Pantee, Ingin Jaya District, Aceh Besar Regency, revealed that 65% of the 40 respondents had hypertension. This highlights a low level of public awareness regarding risk factors and prevention strategies. This community service project aimed to increase knowledge and awareness of hypertension through health education provided by lecturers and students from the Faculty of Public Health at Muhammadiyah University of Aceh. The methods used included coordinating with village officials, preparing educational materials, conducting interactive sessions, and evaluating the participants' understanding. The results showed a significant increase in the community's understanding of hypertension symptoms, causes, and prevention. Participants also demonstrated a new awareness of the importance of adopting a healthy lifestyle and regularly monitoring their blood pressure. The educational sessions not only improved knowledge but also motivated behavioral changes toward a healthier way of living. In conclusion, this project was effective in raising early awareness of hypertension among the community and serves as a crucial first step in reducing the disease's prevalence in Gampong Pantee.